Perancangan Alat Treker Piston Kaliper Rem Mobil Dengan Sistem Hidrolik - Ariambaryana, I Putu Ade; Gunawan, Yuspian; Sisworo, Raden Rinova (Teknik Mesin Universitas Halu Oleo, 2022)
The hydraulic piston tracker is a tool used to press the car's caliper pistons when changing the disc pad. This study aims to design and design a piston caliper treker tool with a maximum strength of 50Kg and to determine the components and dimensions used in this tool. In this study, the main system is hydraulic which converts the pressure to be greater. The pressure produced by this tool is 50Kg or 490.5 N using only the force of the hand of 8.05 N. For the size of this tool it has an overall length of 27 cm, a retaining width of 11.5 cm, a lever length of 20 cm and a hydraulic tube diameter. 3 cm. main material for hydraulic cylinder chrome steel s30c 48 (Kg/mm2), low carbon steel plate (ST42) 36 (Kg/mm2), bolts, handles and levers Low carbon steel (ST42) 36 (Kg/mm2).Key words : Tool, Treker, design, hydraulic